# RD Sharma Solutions for Class 8 Math Chapter 6 - Algebraic Expressions and Identities (Part-5 ) Notes | Study RD Sharma Solutions for Class 8 Mathematics - Class 8

## Class 8: RD Sharma Solutions for Class 8 Math Chapter 6 - Algebraic Expressions and Identities (Part-5 ) Notes | Study RD Sharma Solutions for Class 8 Mathematics - Class 8

The document RD Sharma Solutions for Class 8 Math Chapter 6 - Algebraic Expressions and Identities (Part-5 ) Notes | Study RD Sharma Solutions for Class 8 Mathematics - Class 8 is a part of the Class 8 Course RD Sharma Solutions for Class 8 Mathematics.
All you need of Class 8 at this link: Class 8

(x) (a2b − bc2)

(xii) (x2 − ay)

#### Answer 1: We will use the identities (a+b)2=a2+2ab+b2 and (a−b)2=a2−2ab+b2a+b2=a2+2ab+b2 and a-b2=a2-2ab+b2 to convert the squares of binomials as trinomials.

(i) (x+2)2=x2+2×x×2+b2=x2+4x+b2

(ii) (8a+3b)2=(8a)2+2(8a)(3b)+(6b)2=64a2+48ab+36b2(iii) (2m+1)2=(2m)2+2(2m)(1)+12=4m2+4m+1

(iv) (9a+1/6)2=(9a)2+2(9a)(1/6)+(1/6)2=81a2+3a+1/36

(x) (a2bbc2)2=(a2b)22(a2b)(bc2)+(bc2)2=a4b22a2b2c2+b2c4

(xii) (x2ay)2=(x2)22x2(ay)+(ay)2=x42x2ay+a2y2

#### Question 2: Find the product of the following binomials:(i) (2x + y)(2x + y)(ii) (a + 2b)(a − 2b)(iii) (a2 + bc)(a2 − bc)

(vi) (2a3 + b3)(2a3 − b3)

#### Answer 2: (i) We will use the identity (a+b)2=a2+2ab+b2a+b2=a2+2ab+b2  in the given expression to find the product.(2x+y)(2x+y)=(2x+y)2=(2x)2+2(2x)(y)+y2=4x2+4xy+y2(ii) We will use the identity (a+b)(a−b)=a2−b2a+ba-b=a2-b2 in the given expression to find the product.(a+2b)(a−2b)=a2−(2b)2=a2−4b2(iii) We will use the identity (a+b)(a−b)=a2−b2a+ba-b=a2-b2 in the given expression to find the product.(a2+bc)(a2−bc)=(a2)2−(bc)2=a4−b2c2(iv)We will use the identity (a+b)(a−b)=a2−b2a+ba-b=a2-b2 in the given expression to find the product.

(v) We will use the identity (a+b)(ab)=a2b2a+ba-b=a2-b2 in the given expression to find the product.

(vi) We will use the identity (a+b)(ab)=a2b2a+ba-b=a2-b2 in the given expression to find the product.
(2a3+b3)(2a3b3)=(2a3)2(b3)2=4a6b6 (vii) We will use the identity (a+b)(ab)=a2b2a+ba-b=a2-b2 in the given expression to find the product.

(viii) We will use the identity (a+b)(ab)=a2b2a+ba-b=a2-b2 in the given expression to find the product.